Correlation Between Post-operative Sense of Coherence and Family Function in Patients With Type A Aortic Dissection - Zhang, Xiaomin; Chen, Juan; Zang, Yaning (Frontiers in Surgery, 2022)
Objective To analyze the relationship between the postoperative sense of coherence and []family function in patients with type A aortic dissection (AD). Methods Ninety patients with AD treated from January 2019 to December 2020 were selected as the research subjects. All patients received surgical treatments. Two weeks after the operation, the sense of coherence scale (SOC-13) and family APGAR index scale (APGAR) were used to evaluate the patients’ sense of coherence and family function. Baseline data of all patients were collected, the SOC-13 scores of patients with type A AD with different data characteristics were compared, and the relationship between family function and patients’ sense of coherence was mainly analyzed. Results The levels of sense of coherence of 90 patients with type A AD was average, and the average score of SOC-13 was (49.84±3.89) points; the SOC-13 score of patients with type A AD with family monthly incomes <5000 yuan, moderate and severe family dysfunction was lower than that of patients with family monthly incomes ≥5000 yuan and good family function, the difference was statistically significant (P<0.05); there was no statistically significant difference in the SOC-13 scores of patients with type A AD with different data characteristics (P>0.05); by multiple linear regression analysis, the results showed that family monthly incomes <5000 yuan, moderate and severe family dysfunction might be the general influencing factors of sense of coherence of patients with type A AD (P<0.05), the Y=43.333+6.667X1+16.730X2 was obtained. Conclusion The postoperative sense of coherence of patients with type A AD may be affected by family function.